Preparation method and application of solid spherical sodium ferrous sulfate composite positive electrode material

The preparation of solid spherical sodium ferrous sulfate composite cathode material through metallurgical waste is solved, and the problem of insufficient performance of sodium ferrous sulfate cathode material is achieved, achieving efficient and environmentally friendly material preparation and excellent battery performance.

CN119461493AActive Publication Date: 2025-02-18KUNMING UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411620996.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

Smart Images

  • Figure CN119461493A_ABST
    Figure CN119461493A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a solid spherical sodium ferrous sulfate composite positive electrode material. The preparation method comprises the following steps: 1, adding a conductive carbon material into deionized water, and carrying out ultrasonic treatment to obtain a conductive carbon solution; ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate prepared on the basis of hematite sediment are added into deionized water respectively and stirred, and a light blue solution is obtained; pouring the conductive carbon solution into the light blue solution according to a mass ratio of 1: 1, and stirring to obtain a precursor solution; 2, carrying out spray drying treatment on the precursor solution to obtain an intermediate phase; and 3, uniformly grinding the intermediate phase, placing the intermediate phase in a tubular furnace, and calcining the intermediate phase in an inert atmosphere to obtain the solid spherical sodium ferrous sulfate composite positive electrode material. The sodium ferrous sulfate composite positive electrode material prepared by the preparation method disclosed by the invention has a uniform and continuous conductive network, so that the intrinsic electron conductivity and the sodium ion transmission rate of the sodium ferrous sulfate are enhanced, the cycling stability of the material is improved, and waste reutilization is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion battery positive electrode materials, and specifically relates to a preparation method and application of a solid spherical sodium ferrous sulfate composite positive electrode material. Background Art

[0002] With the growth of energy storage demand, lithium-ion batteries are increasingly used in social life. However, lithium resources are in short supply and unevenly distributed on the earth, and with the widespread application of lithium-ion batteries, the cost is getting higher and higher. Compared with lithium resources, sodium resources are abundant. The content of lithium in the earth's crust is only 0.0065%, while the content of sodium is 2.75%, which is more than 400 times that of the former. Sodium-ion batteries have similar electrochemical reaction mechanisms to lithium-ion batteries, making sodium-ion batteries an ideal supplement to lithium-ion batteries. The positive electrode material is one of the key components of sodium-ion batteries, which greatly affects the energy density and power density of the battery. The development of positive electrode materials determines the application of sodium-ion batteries.

[0003] Among the numerous cathode materials for sodium-ion batteries, polyanionic compounds are considered to be the most promising class of electrode materials due to their excellent structural stability, safety, and high voltage platform. Among them, sodium ferrous sulfate cathode material has become an ideal choice for sodium-ion battery cathode materials due to its low cost, non-toxicity, special three-dimensional sodium ion diffusion channels, and high voltage platform. However, the larger band gap poses a challenge to the transition of electrons from the valence band to the conduction band, resulting in a decrease in the intrinsic carrier concentration, which leads to slow kinetics and poor rate performance.

[0004] The methods reported so far to improve the kinetic and rate performance of sodium ferrous sulfate mainly include effective strategies such as doping, carbon coating, and construction of a well-structured carbon network. Although these methods have opened up broad avenues for improving sodium storage, the improvement of ion / electron transport is still limited. In addition, the complex operation process and the use of toxic reagents have seriously hindered the commercialization process. At present, spray drying technology obtains high-purity and high-activity cathode materials by rapidly drying the solution into powder. Therefore, the selection of a simple and environmentally friendly preparation method is crucial to achieve high-performance and scalable sodium ferrous sulfate cathode materials. Considering that a large amount of hematite slag is generated in the metallurgical industry, it can be prepared into high-purity ferrous sulfate heptahydrate by a wet process, and the production of sodium ferrous sulfate cathode materials consumes a large amount of ferrous sulfate heptahydrate, so the high-value reuse of metallurgical waste slag will form a closed-loop design of waste and new energy materials. Summary of the invention

[0005] The present invention is intended to provide a preparation method and application of a solid spherical sodium ferrous sulfate composite positive electrode material. The use of metallurgical waste as raw materials can greatly reduce production costs, the experimental process is simple and the production efficiency is high, and the use of simple carbon composites can effectively improve the problems of low intrinsic electronic conductivity and poor rate performance of sodium ferrous sulfate. The battery capacity used for sodium ion batteries is high and the cycle performance is excellent.

[0006] The first aspect of the present invention provides a method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material, the steps of which are as follows:

[0007] Step 1: Add the conductive carbon material to deionized water, and ultrasonicate for 6-12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid, anhydrous sodium sulfate, and ferrous sulfate heptahydrate prepared based on hematite sediment to deionized water respectively, and stir on a magnetic stirrer to obtain a light blue solution; then pour the conductive carbon solution into the light blue solution in a mass ratio of 1:1 and stir to obtain a precursor solution;

[0008] Step 2: spray drying the precursor solution to obtain an intermediate phase;

[0009] Step 3: Grind the intermediate phase evenly and place it in a tube furnace, and calcine it under inert atmosphere to obtain a solid spherical sodium ferrous sulfate composite positive electrode material.

[0010] In one embodiment, the rotation speed of the magnetic stirrer is 300-1000 rpm, and the stirring time on the magnetic stirrer is 1-10 h.

[0011] In one embodiment, the ferrous sulfate heptahydrate prepared based on hematite sludge is characterized in that the preparation method is a wet production process, specifically including leaching, reduction and crystallization.

[0012] In one embodiment, the conductive carbon material is any one or more of Ketjen black, carbon nanotubes, graphene, acetylene black, graphite, and Super P (conductive carbon black); the composite mass of the conductive carbon material is 3%-10% of the mass of the sodium ferrous sulfate positive electrode material.

[0013] In one embodiment, the stoichiometric ratio of anhydrous sodium sulfate to ferrous sulfate heptahydrate is 2:(3-4).

[0014] In one embodiment, the mass of the ascorbic acid is 20%-60% of the mass of the ferrous sulfate heptahydrate.

[0015] In one embodiment, the spray drying temperature is set to 180-250°C; the calcination temperature is 350-400°C; the calcination time is 8-18h;

[0016] In one embodiment, the inert atmosphere is one of argon, nitrogen, and a mixture of an inert gas and a reducing gas.

[0017] In a second aspect, the present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode and the negative electrode are located on both sides of the separator, and the electrolyte is located between the positive electrode and the negative electrode. The positive electrode is a positive electrode sheet prepared by using the solid spherical sodium ferrous sulfate composite positive electrode material prepared by the preparation method of the solid spherical sodium ferrous sulfate composite positive electrode material described above, and the positive electrode sheet is a round sheet with a diameter of 14 mm; the negative electrode is a sodium metal sheet, wherein the diameter of the sodium metal sheet is 16 mm and the thickness is 0.2 to 0.4 mm; the electrolyte is 0.1 mL of a sodium perchlorate / ethylene carbonate / propylene carbonate / fluoroethylene carbonate solution with a concentration of 1 mol / L; and the separator is a glass fiber separator with a diameter of 19 mm.

[0018] Beneficial effects of the present invention:

[0019] (1) The solid spherical sodium ferrous sulfate composite positive electrode material prepared by the present invention has a simple operation method, a high safety factor, is suitable for large-scale production, and the prepared material has a high battery capacity and excellent cycle stability.

[0020] (2) The present invention adopts a spray drying method to prepare a solid spherical sodium ferrous sulfate composite positive electrode material. The obtained intermediate phase is Na2Fe(SO4)2·4H2O, which can be transformed into the target sodium ferrous sulfate positive electrode material by simply controlling the temperature and humidity. The spray drying method used is conducive to the formation of a spherical morphology and reduces the calcination time.

[0021] (3) The present invention proposes to use conductive carbon materials for in-situ compounding, which is self-assembled with sodium ferrous sulfate to form a dense solid spherical structure, effectively improving the cyclic stability of the material.

[0022] (4) The raw materials for preparing the solid spherical sodium ferrous sulfate composite positive electrode material of the present invention are cheap and abundant in source, and are suitable for large-scale industrial production.

[0023] (5) The conductive carbon material provided by the technical solution of the present invention is evenly mixed with the sodium ferrous sulfate positive electrode material, and the rate performance of the material is significantly improved.

[0024] (6) The technical solution of the present invention realizes the organic combination of metallurgical waste slag and new energy, reduces environmental pollution and lowers the production cost of sodium ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a schematic flow chart of a method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention.

[0027] Figure 2 This is the (XRD) diagram of the sodium ferrous sulfate positive electrode material prepared in Comparative Example 1 without adding conductive carbon material.

[0028] Figure 3 This is a cycle performance diagram of a sodium ion battery prepared with the sodium ferrous sulfate positive electrode material prepared in Comparative Example 1 without adding conductive carbon material at a C / 5 rate.

[0029] Figure 4 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate positive electrode material prepared in Comparative Example 1 without adding conductive carbon material.

[0030] Figure 5 This is the (XRD) diagram of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 1.

[0031] Figure 6 This is a cycle performance diagram of a sodium ion battery prepared using the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 1 at a C / 5 rate.

[0032] Figure 7 This is a scanning electron microscope (SEM) image of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 1.

[0033] Figure 8 This is the (XRD) diagram of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 2.

[0034] Fig. 9 This is a cycle performance diagram of a sodium ion battery prepared using the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 2 at a C / 5 rate.

[0035] Fig.10 This is a scanning electron microscope (SEM) image of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 2.

[0036] Fig.11 This is the XRD diagram of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 3.

[0037] Fig.12 This is a cycle performance diagram of a sodium ion battery prepared using the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 3 at a C / 5 rate.

[0038] Fig.13 This is a scanning electron microscope (SEM) image of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 3.

[0039] Fig.14 This is a scanning electron microscope (SEM) image of a sodium ion battery prepared with the sodium ferrous sulfate positive electrode material prepared in Comparative Example 2 without adding conductive carbon material after cycling at a C / 5 rate.

[0040] Fig.15 This is a transmission electron microscope (TEM) image of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 4. DETAILED DESCRIPTION

[0041] Hereinafter, a method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material of the present invention will be described in detail in conjunction with exemplary embodiments.

[0042] See also Figure 1 , Figure 1 The present invention provides a method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying. The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying comprises the following steps:

[0043] S1: Add the conductive carbon material into deionized water and ultrasonicate for 6-12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate prepared based on hematite sediment into deionized water respectively, and stir them on a magnetic stirrer to obtain a light blue solution; then pour the conductive carbon solution into the light blue solution in a mass ratio of 1:1 and stir to obtain a precursor solution;

[0044] S2: spray drying the precursor solution to obtain an intermediate phase;

[0045] S3: Grind the intermediate phase evenly and place it in a tube furnace, and calcine it under an inert atmosphere to obtain a solid spherical sodium ferrous sulfate composite positive electrode material.

[0046] Specifically, the ultrasonic time in step S1 is 6-12 h, that is, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, or other values ​​within the above range.

[0047] The wet process used to prepare ferrous sulfate heptahydrate from hematite sludge in step S1 specifically includes leaching, reduction and crystallization.

[0048] The rotation speed of the magnetic stirrer in step S1 is 300-1000 rpm, that is, it can be 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, or other values ​​within the above range.

[0049] The stirring time of the magnetic stirrer in step S1 is 1-10 h, that is, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or other values ​​within the above range.

[0050] The mass ratio of the added deionized water to the added conductive carbon material in step S1 is (4-7):1, that is, it can be 4:1, 5:1, 6:1, 7:1, or other ratios within the above range.

[0051] The mass ratio of the added deionized water to the sodium ferrous sulfate precursor in step S1 is (4-7):1, that is, it can be 4:1, 5:1, 6:1, 7:1, or other ratios within the above range.

[0052] The conductive carbon material in step S1 may be any one or more of Ketjen black, carbon nanotubes, graphene, acetylene black, graphite, and SuperP (conductive carbon black);

[0053] The mass of the conductive carbon material composite in step S1 is 3%-10% of the mass of the sodium ferrous sulfate positive electrode material, that is, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or other values ​​within the above range.

[0054] The stoichiometric ratio of anhydrous sodium sulfate to ferrous sulfate heptahydrate in step S1 is 2:(3-4), that is, it can be 2:3, 2:3.2, 2:3.4, 2:3.6, 2:3.8, 2:4, or other values ​​within the above range.

[0055] The mass of ascorbic acid in step S1 is 20%-60% of the mass of ferrous sulfate heptahydrate added, that is, it can be 20%, 30%, 40%, 50%, 60%, or other values ​​within the above range.

[0056] The spray drying temperature in step S2 is set to 180-250°C, that is, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or other values ​​within the above range.

[0057] The calcination temperature in step S3 is 350-400°C, that is, it can be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or other values ​​within the above range.

[0058] The calcination time in step S3 is 8-18 hours, that is, it can be 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, or other values ​​within the above range.

[0059] The inert atmosphere in step S2 is one of argon, nitrogen, and a mixture of an inert gas and a reducing gas.

[0060] In this embodiment, the aforementioned solid spherical sodium ferrous sulfate composite positive electrode material preparation method is used to in-situ composite with a conductive carbon material when preparing a sodium ferrous sulfate solution, and self-assembles to form a dense solid spherical structure, which effectively improves the material's cycle stability. The added conductive carbon material forms an efficient conductive network, which effectively improves the material's electronic conductivity and rate performance.

[0061] On the basis of the foregoing, this embodiment also provides a sodium ion battery prepared by a solid spherical sodium ferrous sulfate composite positive electrode material prepared by spray drying, comprising a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the positive electrode and the negative electrode are located on both sides of the diaphragm, and the electrolyte is located between the positive electrode and the negative electrode, characterized in that the positive electrode is a positive electrode sheet prepared by the carbon composite ferrous sulfate positive electrode material, and the positive electrode sheet is a round sheet with a diameter of 14 mm; the negative electrode is a sodium metal sheet, wherein the diameter of the sodium metal sheet is 16 mm and the thickness is 0.2 to 0.4 mm; the electrolyte is 0.1 mL of a sodium perchlorate / ethylene carbonate / propylene carbonate / fluoroethylene carbonate solution with a concentration of 1 mol / L; and the diaphragm is a glass fiber diaphragm with a diameter of 19 mm.

[0062] The solid spherical sodium ferrous sulfate composite positive electrode material prepared according to the preparation method of this embodiment is applied to a sodium ion battery, so that the solid spherical sodium ferrous sulfate composite electrode sheet prepared by the above preparation method also has the advantages of a solid spherical sodium ferrous sulfate composite positive electrode material.

[0063] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0064] Comparative Example 1

[0065] The present invention discloses a method for preparing a solid spherical sodium ferrous sulfate positive electrode material by spray drying, comprising the following steps:

[0066] Step 1: Ascorbic acid accounting for 20% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3 are added to deionized water respectively, wherein the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, and the mass ratio of the added deionized water to the mass of the sodium ferrous sulfate precursor is 5:1, and the mixture is fully stirred on a magnetic stirrer for 1 hour to obtain a light blue solution, thereby obtaining a precursor solution;

[0067] Step 2: spray drying the precursor solution obtained in step 1 at 200° C. to obtain an intermediate phase;

[0068] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate positive electrode material.

[0069] This comparative example prepares a solid spherical sodium ferrous sulfate positive electrode material that is not composited with conductive carbon material. The obtained sodium ferrous sulfate positive electrode material is used to prepare a positive electrode sheet. The positive electrode sheet is made by cutting a slurry coated on an aluminum foil after vacuum drying at 120°C. The slurry is made by mixing the positive electrode material with conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, and then adding 1-methyl-2-pyrrolidone dispersant. 1M NaClO4 is dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is a stainless steel shell, the negative electrode is a metal sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber diaphragm to assemble into a button battery.

[0070] Figure 2 The sodium ferrous sulfate (Na 2.5 Fe 1.75 (SO4)3) X-ray diffraction (XRD) pattern of positive electrode material. It can match the standard X-ray diffraction standard card of sodium ferrous sulfate, that is, Na 2.5 Fe 1.75 (SO4)3.

[0071] Figure 3 This is a cycle performance test of button cells assembled with sodium ferrous sulfate positive electrode materials without composite conductive carbon materials in the voltage range of 2.0 to 4.5V. The first discharge capacity is about 68mAh / g under C / 5 rate conditions.

[0072] Figure 4 It is sodium ferrous sulfate (Na 2.5 Fe 1.75 (SO4)3) Scanning electron microscope (SEM) image of the positive electrode material. It can be seen that the spray drying method can prepare a solid spherical sodium ferrous sulfate positive electrode material with a rough surface. The spherical structure is formed by self-assembly of sodium ferrous sulfate particles.

[0073] Example 1

[0074] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps:

[0075] Step 1: Add 5% of the mass of sodium ferrous sulfate to Ketjen black in deionized water, the mass ratio of deionized water to Ketjen black is 5:1, and ultrasonicate for 12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid accounting for 20% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3 to deionized water, respectively, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the sodium ferrous sulfate precursor is 5:1, and stir well on a magnetic stirrer for 1 hour to obtain a light blue solution, and then pour the uniformly dispersed conductive carbon solution into the light blue solution and mix and stir for 30 minutes to obtain a precursor solution;

[0076] Step 2: spray drying the precursor solution obtained in step 1 at 200° C. to obtain an intermediate phase;

[0077] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0078] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0079] Figure 5 This is the X-ray diffraction (XRD) pattern of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 1. It can match the standard X-ray diffraction standard card of sodium ferrous sulfate, that is, the Na 2.5 Fe 1.75 (SO4)3, indicating that the in-situ composite Ketjen black will not affect the sodium ferrous sulfate (Na 2.5 Fe 1.75 Synthesis of (SO4)3).

[0080] like Figure 6 As shown, the button cell assembled with sodium ferrous sulfate positive electrode material composited with 5% Ketjen black has a first discharge capacity of about 89 mAh / g under C / 5 rate conditions in the voltage range of 2.0-4.5 V. Compared with comparative example 1, the discharge capacity of the material is increased by about 21 mAh / g, and the cycle stability is significantly improved. This is because the added Ketjen black provides an efficient conductive carbon network, which effectively improves the electronic conductivity of the material.

[0081] Figure 7 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate positive electrode material composited with Ketjen black. It can be seen that the Ketjen black and the sodium ferrous sulfate positive electrode material are evenly mixed and self-assembled to form a solid spherical sodium ferrous sulfate composite positive electrode material with a dense structure and a smooth surface.

[0082] Example 2

[0083] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps:

[0084] Step 1: Add 5% of the mass of carbon nanotubes to the mass of sodium ferrous sulfate into deionized water, the mass ratio of deionized water to carbon nanotubes is 5:1, and ultrasonicate for 12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid accounting for 20% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3 into deionized water respectively, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the mass of the sodium ferrous sulfate precursor is 5:1, and stir well on a magnetic stirrer for 1 hour to obtain a light blue solution, and then pour the uniformly dispersed conductive carbon solution into the light blue solution and mix and stir for 30 minutes to obtain a precursor solution;

[0085] Step 2: spray drying the precursor solution obtained in step 1 at 200° C. to obtain an intermediate phase;

[0086] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0087] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0088] Figure 8 This is the X-ray diffraction (XRD) pattern of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 2. It can match the standard X-ray diffraction standard card of sodium ferrous sulfate, that is, the Na 2.5 Fe 1.75 (SO4)3, which shows that the in-situ composite carbon nanotubes will not affect the sodium ferrous sulfate (Na 2.5 Fe 1.75 Synthesis of (SO4)3).

[0089] like Fig. 9 As shown, the button cell assembled with sodium ferrous sulfate positive electrode material composited with 5% carbon nanotubes has an initial discharge capacity of about 80 mAh / g at C / 5 rate in the voltage range of 2.0-4.5 V. Compared with comparative example 1, the discharge capacity of the material is increased by about 12 mAh / g, and the cycle stability is significantly improved. This is because the added carbon nanotubes provide an efficient conductive carbon network, which effectively improves the electronic conductivity of the material.

[0090] Fig.10 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate cathode material composited with carbon nanotubes. It can be seen that the carbon nanotubes and the sodium ferrous sulfate cathode material are evenly mixed and self-assembled to form a solid spherical sodium ferrous sulfate composite cathode material with a dense structure and a smooth surface. However, it can be seen that it is difficult for the carbon nanotubes to be evenly mixed with the sodium ferrous sulfate, and the carbon nanotubes are partially over-aggregated.

[0091] Example 3

[0092] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps:

[0093] Step 1: Add 5% of the mass of reduced graphene oxide to the mass ratio of sodium ferrous sulfate to the mass ratio of reduced graphene oxide to be 5:1, and ultrasonicate for 12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid accounting for 20% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3 to deionized water, respectively, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the mass ratio of sodium ferrous sulfate precursor to be 5:1, and stir well on a magnetic stirrer for 1 hour to obtain a light blue solution, and then pour the uniformly dispersed conductive carbon solution into the light blue solution and mix and stir for 30 minutes to obtain a precursor solution;

[0094] Step 2: spray drying the precursor solution obtained in step 1 at 200° C. to obtain an intermediate phase;

[0095] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0096] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0097] Fig.11 This is the X-ray diffraction (XRD) pattern of the solid spherical sodium ferrous sulfate composite positive electrode material prepared in Example 3. It can match the standard X-ray diffraction standard card of sodium ferrous sulfate, that is, the Na 2.5 Fe 1.75 (SO4)3, which indicates that in situ composite reduction of graphene oxide will not affect the sodium ferrous sulfate (Na 2.5 Fe 1.75 Synthesis of (SO4)3).

[0098] like Fig.12 As shown, the button cell assembled with sodium ferrous sulfate positive electrode material composited with 5% reduced graphene oxide has a first discharge capacity of about 78 mAh / g under C / 5 rate conditions in the voltage range of 2.0-4.5 V, and the discharge specific capacity of the material is increased by about 10 mAh / g compared with comparative example 1. This is because the added reduced graphene oxide provides an efficient conductive carbon network, which improves the electronic conductivity of the material.

[0099] Fig.13 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate positive electrode material composited with reduced graphene oxide. It can be seen that the reduced graphene oxide and the sodium ferrous sulfate positive electrode material form a solid spherical sodium ferrous sulfate composite positive electrode material with a rough surface, the reduced graphene oxide is locally transitionally aggregated, and the reduced graphene oxide is a layered structure that is difficult to mix evenly with sodium ferrous sulfate, which may be the reason for the limited improvement in the capacity of sodium ferrous sulfate.

[0100] Comparative Example 2

[0101] The present invention discloses a method for preparing a solid spherical sodium ferrous sulfate positive electrode material by spray drying, comprising the following steps:

[0102] Step 1: Ascorbic acid accounting for 30% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3.5 are added to deionized water respectively, wherein the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, and the mass ratio of the added deionized water to the mass of the sodium ferrous sulfate precursor is 4:1, and the mixture is fully stirred on a magnetic stirrer for 1 hour to obtain a light blue solution, thereby obtaining a precursor solution;

[0103] Step 2: spray drying the precursor solution obtained in step 1 at 220° C. to obtain an intermediate phase;

[0104] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate positive electrode material.

[0105] This comparative example prepares a solid spherical sodium ferrous sulfate positive electrode material that is not composited with conductive carbon material. The obtained sodium ferrous sulfate positive electrode material is used to prepare a positive electrode sheet. The positive electrode sheet is made by cutting a slurry coated on an aluminum foil after vacuum drying at 120°C. The slurry is made by mixing the positive electrode material with conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, and then adding 1-methyl-2-pyrrolidone dispersant. 1M NaClO4 is dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is a stainless steel shell, the negative electrode is a metal sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber diaphragm to assemble into a button battery.

[0106] Fig.14 This is a scanning electron microscope (SEM) image of a sodium ion battery prepared with the sodium ferrous sulfate positive electrode material prepared in Example 2 without adding conductive carbon material after cycling at a C / 5 rate. It can be seen that the solid sphere is slightly broken after the cycle, and it is proved that the prepared material is a solid spherical structure.

[0107] Example 4

[0108] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps: Step 1: adding 7% of the mass of sodium ferrous sulfate to Ketjen black in deionized water, the mass ratio of the deionized water to the Ketjen black is 4:1, ultrasonicating for 12 hours, and obtaining a uniformly dispersed conductive carbon solution; ascorbic acid accounting for 30% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3.5 are respectively added to the deionized water, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the sodium ferrous sulfate precursor is 4:1, and the mixture is fully stirred on a magnetic stirrer for 1 hour to obtain a light blue solution, and then the uniformly dispersed conductive carbon solution is poured into the light blue solution and mixed and stirred for 30 minutes to obtain a precursor solution;

[0109] Step 2: spray drying the precursor solution obtained in step 1 at 220° C. to obtain an intermediate phase;

[0110] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0111] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0112] like Fig.15 As shown, it is a transmission electron microscope (TEM) image of the sodium ferrous sulfate composite positive electrode material, which shows that the synthesized sodium ferrous sulfate composite material is a solid spherical structure.

[0113] Example 5

[0114] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps:

[0115] Step 1: Add 7% of the mass of carbon nanotubes to the mass of sodium ferrous sulfate into deionized water, the mass ratio of the deionized water to the mass of the carbon nanotubes is 4:1, and ultrasonicate for 12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid accounting for 30% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3.5 into deionized water respectively, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the mass of the sodium ferrous sulfate precursor is 4:1, and stir on a magnetic stirrer for 2 hours to obtain a light blue solution, and then pour the uniformly dispersed conductive carbon solution into the light blue solution and mix and stir for 30 minutes to obtain a precursor solution;

[0116] Step 2: spray drying the precursor solution obtained in step 1 at 220° C. to obtain an intermediate phase;

[0117] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0118] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0119] Example 6

[0120] The method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material by spray drying provided in an embodiment of the present invention comprises the following steps:

[0121] Step 1: Add 7% of the mass of reduced graphene oxide to the mass ratio of sodium ferrous sulfate to the mass ratio of reduced graphene oxide to deionized water, and ultrasonicate for 12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid accounting for 30% of the mass of ferrous sulfate heptahydrate, anhydrous sodium sulfate and ferrous sulfate heptahydrate in a stoichiometric ratio of 2:3.5 to deionized water, respectively, the ferrous sulfate heptahydrate is prepared by a wet process based on hematite sediment, the mass ratio of the added deionized water to the mass ratio of sodium ferrous sulfate precursor to be 4:1, and stir on a magnetic stirrer for 2 hours to obtain a light blue solution, and then pour the uniformly dispersed conductive carbon solution into the light blue solution and mix and stir for 30 minutes to obtain a precursor solution;

[0122] Step 2: spray drying the precursor solution obtained in step 1 at 220° C. to obtain an intermediate phase;

[0123] Step 3: Grind the intermediate phase evenly and then calcine it in a tubular furnace under argon conditions for 12 hours to obtain a spherical sodium ferrous sulfate composite positive electrode material.

[0124] The solid spherical sodium ferrous sulfate composite positive electrode material prepared in this embodiment is used to prepare the positive electrode plate, using 1M NaClO4 dissolved in ethylene carbonate (EC) / propylene carbonate (PC) / fluoroethylene carbonate (FEC) as the electrolyte, the outer shell is made of stainless steel shell, the negative electrode is made of metallic sodium sheet, and the positive electrode is separated from the negative electrode by a glass fiber separator to be assembled into a button battery.

[0125] Although the present invention has been described above in conjunction with the exemplary embodiments and the accompanying drawings, it should be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.

Claims

1. A method for preparing a solid spherical sodium ferrous sulfate composite positive electrode material, characterized in that: Step 1: Add the conductive carbon material into deionized water and perform ultrasonic treatment for 6-12 hours to obtain a uniformly dispersed conductive carbon solution; add ascorbic acid, anhydrous sodium sulfate and ferrous sulfate heptahydrate prepared based on hematite precipitate into deionized water respectively, and stir well on a magnetic stirrer to obtain a light blue solution; Then, the conductive carbon solution is poured into the light blue solution in a mass ratio of 1:1 and stirred to obtain a precursor solution; Step 2: spray drying the precursor solution to obtain an intermediate phase; Step 3: Grind the intermediate phase evenly and place it in a tube furnace, and calcine it under inert atmosphere to obtain a solid spherical sodium ferrous sulfate composite positive electrode material.

2. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The size of the solid spherical sodium ferrous sulfate composite positive electrode material particles is 0.5-10 microns.

3. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The ferrous sulfate heptahydrate described in step 1 is prepared by a wet production process based on hematite sludge, and the wet production process includes leaching, reduction and crystallization.

4. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: In step 1, the rotation speed of the magnetic stirrer is 300-1000 rpm, and the stirring time is 1-10 h.

5. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The conductive carbon material is at least one of Ketjen black, carbon nanotubes, graphene, acetylene black, graphite, and Super P (conductive carbon black).

6. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The mass of the conductive carbon material added is 3%-10% of the mass of the obtained sodium ferrous sulfate composite positive electrode material.

7. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The stoichiometric ratio of the anhydrous sodium sulfate to the ferrous sulfate heptahydrate is 2:(3-4); the added mass of the ascorbic acid is 20%-60% of the mass of the ferrous sulfate heptahydrate.

8. The method for preparing the solid spherical sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The spray drying temperature is set to 180-250° C.; the calcination temperature is 350-400° C.; the calcination time is 8-18 hours; and the inert atmosphere is argon or nitrogen or a mixture of an inert gas and a reducing gas.

9. A solid spherical sodium ferrous sulfate composite positive electrode material, characterized in that: The solid spherical sodium ferrous sulfate composite positive electrode material is prepared by the preparation method of the solid spherical sodium ferrous sulfate composite positive electrode material according to any one of claims 1 to 8.

10. A sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode and the negative electrode are located on both sides of the separator, and the electrolyte is located between the positive electrode and the negative electrode, characterized in that: The positive electrode is a positive electrode sheet prepared by a solid spherical sodium ferrous sulfate composite positive electrode material prepared by the preparation method of a solid spherical sodium ferrous sulfate composite positive electrode material as described in any one of claims 1 to 8, and the positive electrode sheet is a round sheet with a diameter of 14 mm; the negative electrode is a sodium metal sheet, wherein the diameter of the sodium metal sheet is 16 mm and the thickness is 0.2-0.4 mm; the electrolyte is 0.1 mL of a sodium perchlorate / ethylene carbonate / propylene carbonate / fluoroethylene carbonate solution with a concentration of 1 mol / L; and the diaphragm is a glass fiber diaphragm with a diameter of 19 mm.

Citation Information

Patent Citations

  • Preparation method of Na2Fe (SO4) 2 / C as sodium ion battery composite positive electrode material

    CN115159581A

  • Sodium ferrous sulfate / carbon nanotube composite positive electrode material, preparation method and sodium ion battery

    CN115172724A

  • Lithium / sodium ion battery positive electrode material production waste liquid recovery, and obtained material and application thereof

    CN115594224A

  • In-situ carbon-coated sodium ferrous sulfate composite positive electrode material, preparation and sodium ion battery

    CN116354405A

  • Hollow spherical sodium ferrous sulfate / carbon composite positive electrode material, preparation method and sodium ion battery prepared from hollow spherical sodium ferrous sulfate / carbon composite positive electrode material

    CN117727883A